English speaking activities for raising entrepreneurship awareness: EFL students’ view - Ratnaningsih, Paskalina Widiastuti (English Learning Innovation, 2024)
Speaking is as the part of English skills. Speaking English is important for communication. English is learned in the university level. Entrepreneurship study program students learn English to increase their English related to entrepreneurship. English is needed when they become an entrepreneur for communication. Speaking English well is also needed so that it can convey appropriate meaning. This study aims to discover students’ views on entrepreneurship awareness through speaking English. The method used was survey research. The respondents were students of entrepreneurship study program. The questionnaire consisted of closed-ended questions and open-ended questions. The finding of this research was students’ awareness of entrepreneurship increased in the process of speaking English. The students were motivated to start their businesses. They had mindset and attitude to be an entrepreneur. It was needed as the foundation to start business. Then, they became aware of SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis in starting their businesses. By analyzing SWOT, they became aware of the processes on how to start their businesses. Their speaking skill also increased along with the increase of their vocabulary, grammar, and pronunciation. Their vocabularies in entrepreneurship had increased. They could also use appropriate grammar in context and appropriate pronunciation. Their self-confident in speaking English also increased.